The role of water, sanitation and hygiene interventions in reducing soil-transmitted helminths: interpreting the evidence and identifying next steps. - Vaz Nery, Susana.; Pickering, Amy J.; Abate, Ebba.; Asmare, Abraham.; Barrett, Laura.; Benjamin-Chung, Jade.; Bundy, Donald A.; Clasen, Thomas.; Clements, Archie C.; Colford, John M.; Ercumen, Ayse.; Crowley, Siobhan.; Cumming, Oliver.; Freeman, Matthew C.; Haque, Rashidul.; Mengistu, Birhan.; Oswald, William E.; Pullan, Rachel L.; Oliveira, Rita G.; Einterz Owen, Katey.; Walson, Judd L.; Youya, Ashrafedin.; Brooker, Simon J. (Tufts University. Tisch Library., 2019)
Abstract: The transmission soil transmitted helminths (STH) occurs via ingestion of or contact with infective stages present in soil contaminated with human faeces. It follows therefore that efforts to reduce faecal contamination of the environment should help to reduce risk of parasite exposure and improvements in water, sanitation and hygiene (WASH) are seen as essential for the long-term, sustainable control of STH. However, the link between WASH and STH is not always supported by the available evidence from randomised controlled trials, which report mixed effects of WASH intervention on infection risk. This review critically summarises the available trial evidence and offers an interpretation of the observed heterogeneity in findings. The review also discusses the implications of findings for control programmes and highlights three main issues which merit further consideration: intervention design, exposure assessment, and intervention fidelity assessment.; Keywords: Soil-transmitted helminths, Water, Sanitation, Hygiene, WASH.; Springer Open.